Impasse Choice in the Canadian Federal Service: An Innovation and an Intrigue - Subbarao, A.V. (Relations industrielles / Industrial Relations, 1985)
This paper discusses the effect ofthe Supreme Court's judgement on the impasse choice in the federal public service. The developments which led to innovation in the sixties and intrigue in the eighties are briefly described and analyzed. Important policy changes are suggested in order to restore and preserve the innovative features of the federal public sector collective bargaining System introduced in the sixties.